Adverse events and dropouts in Alzheimer's disease studies: What can we learn?. Issue 1 (10th March 2014) - Henley, David B.; Sundell, Karen L.; Sethuraman, Gopalan; Schneider, Lon S.
Abstract: Background: Interpreting Alzheimer's disease (AD) clinical trial (CT) outcomes is complicated by treatment dropouts and adverse events (AEs). In elderly participants, AE rates, dropouts, and deaths are important considerations as they may undermine the validity of clinical trials. Published discontinuation and safety data are limited. Methods: Safety data from 1054 placebo‐treated participants in IDENTITY and IDENTITY‐2, 76‐week, Phase 3 AD studies conducted in 31 countries, were pooled, annualized, and summarized overall, by country and age group. Results: Median age was 74.2 (interquartile range 67.9–79.5) years; 57.4% were female; and median observation time was 63.2 (interquartile range 41.6–77.4) weeks when study drug dosing was halted. Overall annualized rates for discontinuations, discontinuations due to AEs, serious adverse events (SAEs), and deaths were 21.6% (range 19.6%–24.0%), 8.2% (range 8.1%–8.3%), 12.0%, and 1.7%, respectively. AE and discontinuation rates varied by country and age groups. Fall, pneumonia, and atrial fibrillation AEs were more frequent in the oldest age group. Conclusions: These annualized placebo safety data provide insight into the course of enrolled patients with mild‐to‐moderate AD, and are useful in planning longer term trials and in monitoring safety.